Can stable isotope mass spectrometry replace ‎radiolabelled approaches in metabolic studies?. (August 2016) - Batista Silva, Willian; Daloso, Danilo M.; Fernie, Alisdair R.; Nunes-Nesi, Adriano; Araújo, Wagner L.
Highlights: Metabolism is arguably the best characterized network within biological systems. Metabolic pathways can be deduced in tracer experiments using isotopically labelled substrates. Improved understanding of the metabolic network facilitates metabolic engineering strategies. Stable isotopes more readily provide information at the atomic and molecular level and are generally less laborious. Abstract: Metabolic pathways and the key regulatory points thereof can be deduced using isotopically labelled substrates. One prerequisite is the accurate measurement of the labeling pattern of targeted metabolites. The subsequent estimation of metabolic fluxes following incubation in radiolabelled substrates has been extensively used. Radiolabelling is a sensitive approach and allows determination of total label uptake since the total radiolabel content is easy to detect. However, the incubation of cells, tissues or the whole plant in a stable isotope enriched environment and the use of either mass spectrometry or nuclear magnetic resonance techniques to determine label incorporation within specific metabolites offers the possibility to readily obtain metabolic information with higher resolution. It additionally also offers an important complement to other post-genomic strategies such as metabolite profiling providing insights into the regulation of the metabolic network and thus allowing a more thorough description of plant cellular function. Thus, although safety concerns mean that stable isotope feeding is generally preferred, the techniques are in truth highly complementary and application of both approaches in tandem currently probably provides the best route towards a comprehensive understanding of plant cellular metabolism.